Fermentation of Fruits and Vegetables: Bridging Traditional Wisdom and Modern Science for Food Preservation and Nutritional Value Improvements - Prasad S. Gangakhedkar; Hemant W. Deshpande; Gréta Törős; Hassan El-Ramady; Tamer Elsakhawy; Neama Abdalla; Ayaz Shaikh; Béla Kovács; Rushikesh Mane; József Prokisch (Foods, 2025)
Fermented fruits and vegetables are gaining increased attention due to their enhanced nutritional properties, extended shelf life, and potential health benefits. Driven by consumer demand for natural, plant-based, and functional foods, fermentation is emerging as a sustainable alternative to conventional preservation methods. This review highlights the role of lactic acid bacteria and other microorganisms in transforming fruit and vegetable substrates into probiotic-rich, bioactive foods. It explores traditional and emerging fermentation techniques, the influence of microbial consortia on product quality, and the impact of fermentation on antioxidant activity, gut health, immune modulation, and chronic disease prevention. Furthermore, the review addresses food safety concerns related to biogenic amines, nitrite accumulation, and microbial contamination, describing current solutions involving both conventional and non-thermal processing technologies. By synthesizing recent advances in microbial fermentation science and biotechnological innovations, this paper underscores the potential of fermented fruits and vegetables to contribute to functional food development, dietary diversity, and sustainable food systems.